Analisis Pemberlakuan Pembagian dan Pemisahan Kewenangan di Indonesia (Studi Kepustakaan Terhadap Separated of Powers dan Division of Powers) - Elisa Eka Andriyani (Yayasan Literasi Sains Indonesia, 2022)
The division and separation of authorities in a country is an effort to prevent concentration of authority in one person, this is intended as a prevention so that there is no arbitrariness in the leadership structure of a country, including the Unitary State of the Republic of Indonesia. In general, power is an authority that is obtained by a person or group to act according to its scope. Power in several countries is often divided or separated into several forms, one of which is based on the theory of state power. The research conducted in this article is a qualitative research using literature studies on trusted sources from internet journals supported by other people's research and discussed using their own language which was developed and supported by several research results. Data collection was carried out in this study using observation and internet searches regarding literature studies. The purpose of writing is to find out how the implementation of the division of authority in Indonesia. The results of the discussion are that the separate authorities between the central government and local governments can be a determining factor for a region, both provincial and district/city, to develop or it will become a limiting factor for an area to be able to adapt policies made by its government to the life of its people. The author also suggests that stakeholders who are authorized to run the wheels of government, both central and regional, can return to conducting studies and research regarding this distribution of authority, because each existing region, both provincial and district/city has its own characteristics or characteristics, that can develop and adapt to the needs of existing communities.